Inflation Performance and Constitutional Central Bank Independence : Evidence From Latin America and the Caribbean - Gutierrez, Eva (IMF Working Papers; Working Paper ;, 2003)
This paper explores the relationship between the constitutional entrenchment of central bank independence and inflation performance. Empirical studies for developing countries have not found a relationship between central bank independence, proxied by the "de jure" independence established in the central bank law, and inflation. We argue that the constitution is likely to be better enforced than ordinary statutes owing to its higher legal rank. Our empirical analysis finds that in a sample of Latin American and Caribbean countries, those countries that entrench the independence of the central bank in the constitution have a better inflation performance.